PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DAN KUALITAS LAPORAN KEUANGAN PADA EFISIENSI INVESTASI - Fathaya Aji Aryonanto; Totok Dewayanto (Diponegoro Journal of Accounting, 2022)
The study aims to examine the effect of environmental, social, and governance (ESG) disclosure and financial reporting quality on investment efficiency where the variables used in this study are the dependent variable (investment efficiency), independent variable (ESG disclosure and financial reporting quality), and control variable (tangible, leverage, firm financial performance).The population in this study are non financial companies listed on the Indonesia Stock Exchange in 2018-2020. Sampling is done by purposive sampling. Based on purposive sampling in sample selection, 180 research samples were obtained for three consecutive years (2018-2020). The hypothesis of this research using multiple regression analysis methode.The finding of this study reveal that ESG disclosure non affect the investment efficiency. Meanwhile, financial reporting quality has a positive and significant on investment efficiency.